2020
DOI: 10.1016/j.isci.2020.100949
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Charge Transfer and Adjustable Potential Window in Semiconductor/Faradaic Layer/Liquid Junctions

Abstract: Semiconductor/Faradaic layer/liquid junctions have been widely used in solar energy conversion and storage devices. However, the charge transfer mechanism of these junctions is still unclear, which leads to inconsistent results and low performance of these devices in previous studies. Herein, by using Fe 2 O 3 and Ni(OH) 2 as models, we precisely control the interface structure between the semiconductor and the Faradaic layer and investigate the charge transfer mechanism in the semiconductor/ Faradaic layer/li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…10 Therefore, the intermediate layers can be considered as extrinsic faradaic layers. 11 The faradaic layers can accelerate both interface charge collection and oxygen evolution reaction (OER) kinetics and improve the performance of a photoelectrode. [12][13][14][15] Moreover, some recent studies have suggested that there is an intrinsic hydrated layer on the surface of metal oxide in ambient air or an electrolyte, 6,[16][17][18][19] which also has signicant effects on interface charge separation and transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Therefore, the intermediate layers can be considered as extrinsic faradaic layers. 11 The faradaic layers can accelerate both interface charge collection and oxygen evolution reaction (OER) kinetics and improve the performance of a photoelectrode. [12][13][14][15] Moreover, some recent studies have suggested that there is an intrinsic hydrated layer on the surface of metal oxide in ambient air or an electrolyte, 6,[16][17][18][19] which also has signicant effects on interface charge separation and transfer.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Therefore, the intermediate layers can be considered as extrinsic faradaic layers. 11 The faradaic layers can accelerate both interface charge collection and oxygen evolution reaction (OER) kinetics and improve the performance of a photoelectrode. 12 – 15…”
Section: Introductionmentioning
confidence: 99%
“…The Si/WO 3 /H 2 SO 4(aq) /C exhibits an unbiased output power of 0.8 mW cm −2 in the dark. However, previously reported devices based on battery‐type chemical junctions [1, 13–20] cannot work under zero bias and indicate negligible output power during dark discharge (Supporting Information, Table S1). Therefore, this new capacitor‐type device achieves the highest dark output power among all of the reported two‐electrode solar rechargeable devices.…”
Section: Resultsmentioning
confidence: 99%
“…AF aradaic junction is composed of as emiconductor and aF arador,w hich is ac oupled electron-ion conductor and chemically changed during charge transfer across the interface. [1] Therefore,aFaradaic junction is ac hemical junction and indicates quite different features from some well-known physical junctions,s uch as Schottky junctions, [2][3][4][5] p-n junctions, [6][7][8] or direct Z-scheme junctions, [9][10][11] in which only electrons transfer at the interface (Supporting Information, Figure S1). Very importantly,aFarador in this chemical junction can be regenerated reversibly by controlling the interface charge transfer direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation